2009
DOI: 10.1039/b823236a
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence for interactions between anions and electron-deficient aromatic rings

Abstract: This feature article summarizes our research aimed at using electron-deficient aromatic rings to bind anions in the context of complementary research in this active field. Particular attention is paid to the different types of interactions exhibited between anions and electron-deficient arenes in solution. The 120+ references cited in this article underscore the flurry of recent activity by numerous researchers in this field, which was relatively nascent when our efforts began in 2005. While the interaction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
84
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(85 citation statements)
references
References 122 publications
1
84
0
Order By: Relevance
“…[16] At the same time, recent investigations [16,19] on H 3 O + -and H 5 O 2 + -containing salts have shown that due to the formation of interionic H bonds the positive charge of these species is significantly reduced; this may appear sufficient to involve an oxonium cation into the lp-p binding. Although such interactions are well-known for neutral and negatively charged species, [1][2][3][4] those involving cations as the lp donors have-to the best of our knowledge-not been observed or even proposed yet in the literature.…”
mentioning
confidence: 81%
“…[16] At the same time, recent investigations [16,19] on H 3 O + -and H 5 O 2 + -containing salts have shown that due to the formation of interionic H bonds the positive charge of these species is significantly reduced; this may appear sufficient to involve an oxonium cation into the lp-p binding. Although such interactions are well-known for neutral and negatively charged species, [1][2][3][4] those involving cations as the lp donors have-to the best of our knowledge-not been observed or even proposed yet in the literature.…”
mentioning
confidence: 81%
“…It is worth mentioning that the electrostatic term of anion-p interaction can also be described in terms of ESP as the quantitative predictor of anion-binding energies which are widely used to characterize p-acidity of aromatics and heterocycles. [68,69] For example, ESP maps (Fig. 6) for 1,3,5-trifluorobenzene (TFB), hexafluorobenzene (HFB) .…”
Section: Anion-p Interactionmentioning
confidence: 99%
“…This anion-p interaction is only present in the solid-stateits nonexistence in solution is proved by NMR spectroscopy (vide supra) suggestive of an unhindered rotation of both cyclopentadienyl rings around the Si-C Cp bonds. Since solid-state anion-p interactions can be either of electrostatic nature or of a weak r interaction [17][18][19], we have conducted some DFT studies on the target molecule.…”
Section: Crystal Structure Analyses and Dft Studiesmentioning
confidence: 99%